The Southwestern Historical Quarterly (JSTOR)
The Southwestern Historical Quarterly, continuously published since 1897, is the leading scholarly journal for Texas history and also features content relating to the history of the Greater Southwest. It is offered as a benefit of membership in the Texas State Historical Association.
Keywords: American Studies